Enhancement of heat transfer and product quality using jet reattachment nozzles in drying of food products. Issue 2 (11th January 2022) - Farzad, Milad; El Ferouali, Hicham; Kahraman, Ozan; Yagoobi, Jamal
Abstract: In this paper, the drying characteristics of Radial Jet Reattachment (RJR) and Slot Jet Reattachment (SJR) nozzles, with an exit angle of +45 ∘ for the RJR nozzle and +20 ∘ and +45 ∘ for the SJR nozzle, were experimentally investigated in drying potato chip samples and apple slices, respectively. Dry basis moisture content of the samples using these innovative nozzles were compared to those of traditional nozzles, based on three criteria: identical air mass flow rate, identical fluid flow power, and identical exerted peak surface pressure. To appraise the performance of each nozzle, the corresponding local heat transfer coefficients generated by innovative and traditional nozzles for all the tests were measured. Subsequently, the average heat transfer coefficients of reattachment nozzles were calculated and compared against those of traditional nozzles. Moreover, the kinetics of color changes and structure analysis of apple slices, due to the drying by SJ and SJR + 20 ∘ nozzles were studied. The experimental results revealed that the RJR + 45 ∘ and SJR + 20 ∘ nozzles yield significantly higher drying rates, as well as significant improvement in average heat transfer coefficients, compared to those of ILJ and SJ nozzles, respectively, on a stationary basis. Besides, impingement drying with SJR + 20 ∘ nozzle produced dried apple slices with less color deterioration and fewer nutritional losses compared to drying with the SJ nozzle. Therefore, jet reattachment nozzles can provide faster drying rates and keep the nutritional values at a desirable level.